Aumolertinib: effective treatment for asymptomatic pulmonary giant cell carcinoma with EGFR L858R mutation - a case report - Yang, Wenxing; Yang, Ze; Wang, Kaiqiang; Zhu, Peiquan; Pu, Jiangtao (Frontiers in Oncology, 2023)
Aumolertinib, as a novel third-generation epidermal growth factor receptor tyrosine kinase inhibitor (EGFR-TKI), has been widely employed as a first-line treatment for advanced non-small cell lung cancer (NSCLC) patients with EGFR mutation. However, reports regarding the benefit of using aumolertinib as a monotherapy in pulmonary giant cell carcinoma are relatively scarce. In this report, we present a pulmonary giant cell carcinoma case harboring the EGFR Leu858Arg (L858R) mutation, with the patient at stage cT2bN3M1c IVB. Through the use of autolearning as a single agent, we effectively controlled the progression of pulmonary giant cell carcinoma, achieving a 6-month progression-free survival during the treatment course. Notably, the patient's tumor not only ceased its growth but also continued to shrink, highlighting a significant therapeutic effect. This case reveals the effectiveness of aumolertinib as a monotherapy in controlling disease progression. The finding underscores the therapeutic advantage of aumolertinib in this particular subgroup of patients, offering a novel treatment option for pulmonary giant cell carcinoma.